A method for preparing molybdenum phosphide as a positive electrode of a lithium-carbon dioxide battery
By using trimolybdenum phosphide as the catalyst for the positive electrode of lithium-carbon dioxide batteries, the problem of high charging voltage of lithium-carbon dioxide batteries is solved, low charging voltage and high cycling stability are achieved, and the battery life is extended.
Patent Information
- Application Number
- CN202211409689.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-09
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-11-09
AI Technical Summary
The charging voltage of existing lithium-carbon dioxide batteries is relatively high, which affects the cycling stability and life of the battery. The price of precious metal-based materials is high and it is difficult to replace.
Trimolybdenum phosphide is used as the catalyst for the positive electrode of the lithium-carbon dioxide battery. By treating molybdenum source compound and molybdenum phosphide source oxide precursor, trimolybdenum phosphide without molybdenum element is obtained as a catalyst for replacing precious metals.
The low charging voltage of lithium-carbon dioxide batteries is achieved. The battery charge voltage is as low as 2.93V at a current density of 50mA/g. It can cyclize 40 times at a current density of 250mA/g, and the charging voltage is lower than 4.5V, which improves the battery's magnification and cycling performance and extends the battery's life.
Smart Images

Figure CN115911422B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of new energy storage materials and relates to a method for preparing molybdenum phosphide as a positive electrode of a lithium-carbon dioxide battery. Technical Background
[0002] With the continuous development of energy storage, lithium-ion batteries are no longer sufficient to meet people's needs due to their low energy density, while the energy density of lithium-air batteries is significantly higher than that of other metal gas batteries in the same gas as lithium-ion batteries. In addition, metal-oxygen batteries have higher energy density than the same metal-other gas batteries, so lithium-oxygen seems to be the choice of battery, but metal gas batteries need to work in air, and working only in oxygen is not enough. Li 2 CO 3 It is a stable dielectric product that is not easy to decompose. The key to the reversibility of lithium-carbon dioxide batteries lies in the decomposition of lithium. Too high a charging potential is not conducive to the cycle stability of the battery, so it is very important to reduce the charging voltage of lithium-carbon dioxide batteries.
[0003] Although precious metal-based materials have a good catalytic effect on the decomposition of lithium carbonate and can achieve the purpose of reducing the charging voltage of lithium-carbon dioxide batteries, the price of precious metal materials is often high, and it is necessary to find alternative precious metal-based materials while maintaining the electrocatalytic performance. Some transition metal-based materials with stable catalytic properties have attracted the attention of researchers. It is worth mentioning that although precious metals are part of transition metals, unlike other transition metals, precious metals have stable chemical properties and usually exist in the form of a single substance. Except for precious metals, most transition metals are easy to form compounds due to the presence of unfilled d orbitals. Therefore, transition metal-based materials have greater potential as positive electrode catalysts.
[0004] Molybdenum-based phosphides have not been reported to be used in the field of lithium-carbon dioxide batteries. The present invention provides a method for preparing molybdenum phosphide as a positive electrode of a lithium-carbon dioxide battery. Molybdenum phosphide is obtained by treating a molybdenum source compound and a molybdenum phosphide source oxide precursor, which provides a new idea for using related transition metal-based phosphides as catalysts for energy storage batteries. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing molybdenum phosphide as a positive electrode of a lithium-carbon dioxide battery in order to provide a transition metal-based material with high electrocatalytic performance to replace precious metals.
[0006] The present invention adopts the following technical solutions:
[0007] A method for preparing molybdenum phosphide as a positive electrode of a lithium-carbon dioxide battery comprises the following steps:
[0008] Step a. Add concentrated acid to deionized water in a certain proportion to prepare an acid solution;
[0009] Step b. adding the molybdenum source compound to the acid solution, and ultrasonically dissolving the molybdenum source compound in the acid solution to obtain a mixed solution;
[0010] Step c. Pour the mixed solution in step b into a polytetrafluoroethylene liner, seal the reactor and place it in an oven for heating;
[0011] Step d. The reaction temperature of the oven in step c is 200°C, the reaction time is 20h, and a white molybdenum source oxide precipitate is obtained;
[0012] Step e. placing the molybdenum source oxide obtained in step d downstream of the tubular furnace, and placing the phosphorus source compound upstream of the tubular furnace, wherein the molar ratio of the molybdenum source oxide to the phosphorus source compound is 1:40, heating in an atmosphere of reducing gas and inert gas at a heating temperature of 850°C and a reaction time of 1-4h to obtain molybdenum phosphide.
[0013] Step f. Take molybdenum phosphide and a binder in a mass ratio of 9:1 and mix them in a grinding mortar, grind them evenly for 30 minutes to fully mix the components, and evenly apply them on a carbon material substrate as a positive electrode for a lithium-carbon dioxide battery.
[0014] Step g. Assemble the positive electrode in step f into a button battery, stack the materials in the order of negative electrode shell, spring sheet, gasket, lithium sheet, diaphragm, positive electrode material, stainless steel mesh and positive electrode shell, and seal with a manual hydraulic button battery sealing machine to obtain a button battery.
[0015] In step a, the volume ratio of deionized water to concentrated acid is 5:1, and the concentrated acid is concentrated nitric acid, concentrated sulfuric acid or concentrated nitric acid;
[0016] The molybdenum source compound in step b is ammonium molybdate or sodium molybdate.
[0017] The molybdenum source oxide in step d is molybdenum trioxide.
[0018] The phosphorus source compound in step e is sodium hypophosphite, the reducing gas is hydrogen, and the inert gas is nitrogen or argon.
[0019] The core of the present invention is that the previous transition metal compound catalysts are mainly oxides and nitrides. The present invention uses transition metal phosphides as catalysts for lithium-carbon dioxide battery positive electrodes. In addition, when molybdenum phosphides are synthesized as catalysts, the molybdenum-phosphorus ratio is mainly 1:1. When synthesizing molybdenum-phosphorus trimolybdenum phosphide with a molybdenum-phosphorus ratio of 3:1, molybdenum is often present. This article provides a preparation method for molybdenum-free trimolybdenum phosphide, and uses it for the first time as a catalyst for lithium-carbon dioxide batteries. The material has a relatively low charging voltage, and the charging voltage is as low as 2.93V at a current density of 50mA / g, and can be stably cycled for 40 cycles at a current density of 250mA / g when the charging voltage is lower than 4.5V. The reduction in charging voltage can increase the rate and cycle performance of the battery, thereby achieving the effect of extending the battery life. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 3 is a scanning electron microscope image of molybdenum phosphide in the embodiment.
[0021] Figure 2 This is the XRD pattern of molybdenum phosphide / molybdenum in Example 1.
[0022] Figure 3 This is the XRD pattern of molybdenum phosphide / molybdenum in Example 2.
[0023] Figure 4 This is the XRD pattern of molybdenum phosphide / molybdenum in Example 3.
[0024] Figure 5 It is the XRD spectrum of molybdenum phosphide in the embodiment.
[0025] Figure 6 The figure shows the rate charge and discharge curves of the lithium-carbon dioxide battery in the embodiment at current densities of 50, 100, 200, 300, 400 and 500 mA g-1.
[0026] Figure 7 1 is the cyclic charge and discharge curve of the lithium-carbon dioxide battery in the embodiment at a current density of 250 mA g-1.
[0027] Figure 8 It is a schematic structural diagram of the lithium-carbon dioxide battery of the present invention.
[0028] Description of reference numerals:
[0029] 1-positive electrode cover, 2-spring, 3-gasket, 4-lithium sheet, 5-diaphragm, 6-positive electrode material, 7-stainless steel mesh, 8-positive electrode shell. DETAILED DESCRIPTION
[0030] The specific contents of the present invention are described in detail below in conjunction with specific embodiments:
[0031] Example 1
[0032] Take 10ml of concentrated sulfuric acid and dissolve it in 50ml of deionized water to obtain a sulfuric acid solution. Weigh 1.4g of sodium molybdate and add it to the sulfuric acid solution. Ultrasonicate it in a 500W ultrasonic instrument for 5min to completely dissolve the sodium molybdate and obtain a mixed solution. After the ultrasonication is completed, transfer the mixed solution into a polytetrafluoroethylene liner with a capacity of 100ml and seal it in a reactor. Place the reactor sealed with the mixture in an oven, heat it to 200℃ at a heating rate of 10℃ / min, keep it warm for 20h for hydrothermal reaction, and cool it naturally to room temperature after the reaction is completed. Open the reactor, filter the mixed solution after the reaction, wash it with deionized water 3 times, and dry it in an oven at 70℃ to obtain white molybdenum trioxide powder.
[0033] 72 mg of dried molybdenum trioxide powder and 0.22 g of sodium hypophosphite were placed in two arks respectively, the ark containing molybdenum trioxide powder was placed downstream of the tube furnace, and the ark containing sodium hypophosphite was placed upstream of the tube furnace, and H2 / Ar mixed gas with a flow rate of 100 ml / min and a volume fraction of 7% of H2 was introduced, and the temperature was raised to 100°C at a heating rate of 5°C / min, and the air was evacuated after 30 minutes of heat preservation, and then the temperature was raised to 850°C, and the temperature was kept for 2 hours for conversion reaction. After the reaction, the H2 / Ar mixed gas was turned off, and the mixture was cooled to room temperature under the protection of pure Ar atmosphere to obtain molybdenum phosphide / molybdenum (the mass proportion of molybdenum is 53.4%), and the XRD spectrum is as follows: Figure 2 As shown. Molybdenum phosphide / molybdenum and binder polyvinylidene fluoride were added to a grinding mortar at a mass ratio of 8 to 2, and evenly ground for 30 minutes. The mixture was evenly coated with 0.2 mg of molybdenum phosphide on 1 square centimeter of carbon cloth as the positive electrode of the lithium-carbon dioxide battery. The materials were stacked in the order of negative electrode shell, shrapnel, gasket, lithium sheet, diaphragm, positive electrode material, stainless steel mesh and positive electrode shell, and then sealed with a manual hydraulic button battery sealing machine to obtain a lithium-carbon dioxide button battery.
[0034] The button battery was placed in a test bottle filled with carbon dioxide gas, and a cycle test was carried out at current densities of 50mA / g, 100mA / g, 200mA / g, 300mA / g, 400mA / g and 500mA / g, and a capacity of 500mAh / g. The charging voltage of the battery was less than 4.3V. A cycle test was carried out under the conditions of a current density of 250mA / g and a capacity of 500mAh / g. The battery stably cycled for 95 times when the charging voltage was less than 4.5V.
[0035] Example 2
[0036] Take 10ml of concentrated sulfuric acid and dissolve it in 50ml of deionized water to obtain a sulfuric acid solution. Weigh 1.4g of sodium molybdate and add it to the sulfuric acid solution. Ultrasonicate it in a 500W ultrasonic instrument for 5min to completely dissolve the sodium molybdate and obtain a mixed solution. After the ultrasonication is completed, transfer the mixed solution into a polytetrafluoroethylene liner with a capacity of 100ml and seal it in a reactor. Place the reactor sealed with the mixture in an oven, heat it to 200℃ at a heating rate of 10℃ / min, keep it warm for 20h for hydrothermal reaction, and cool it naturally to room temperature after the reaction is completed. Open the reactor, filter the mixed solution after the reaction, wash it with deionized water 3 times, and dry it in an oven at 70℃ to obtain white molybdenum trioxide powder.
[0037] 72 mg of dried molybdenum trioxide powder and 0.44 g of sodium hypophosphite were placed in two arks respectively, the ark containing molybdenum trioxide powder was placed downstream of the tube furnace, and the ark containing sodium hypophosphite was placed upstream of the tube furnace, and H2 / Ar mixed gas with a flow rate of 100 ml / min and a volume fraction of 7% of H2 was introduced, and the temperature was raised to 100°C at a heating rate of 5°C / min, and the air was evacuated after 30 minutes of heat preservation, and then the temperature was raised to 850°C and kept for 2 hours for conversion reaction. After the reaction was completed, the H2 / Ar mixed gas was turned off, and the mixture was cooled to room temperature under the protection of pure Ar atmosphere to obtain molybdenum phosphide / molybdenum (the mass proportion of molybdenum is 43.4%), and the XRD spectrum is as follows Figure 3 As shown. Molybdenum phosphide / molybdenum and binder polyvinylidene fluoride were added to a grinding mortar at a mass ratio of 8 to 2, and evenly ground for 30 minutes. The mixture was evenly coated with 0.2 mg of molybdenum phosphide on 1 square centimeter of carbon cloth as the positive electrode of the lithium-carbon dioxide battery. The materials were stacked in the order of negative electrode shell, shrapnel, gasket, lithium sheet, diaphragm, positive electrode material, stainless steel mesh and positive electrode shell, and then sealed with a manual hydraulic button battery sealing machine to obtain a lithium-carbon dioxide button battery.
[0038] The button battery was placed in a test bottle filled with carbon dioxide gas, and rate tests were carried out at current densities of 50mA / g, 100mA / g, 200mA / g, 300mA / g, 400mA / g and 500mA / g, and a capacity of 500mAh / g. The charging voltage of the battery was less than 3.5V. A cycle test was carried out under the conditions of a current density of 250mA / g and a capacity of 500mAh / g. The battery stably cycled for 115 times when the charging voltage was less than 4.5V.
[0039] Example 3
[0040] Take 10ml of concentrated sulfuric acid and dissolve it in 50ml of deionized water to obtain a sulfuric acid solution. Weigh 1.4g of sodium molybdate and add it to the sulfuric acid solution. Ultrasonicate it in a 500W ultrasonic instrument for 5min to completely dissolve the sodium molybdate and obtain a mixed solution. After the ultrasonication is completed, transfer the mixed solution into a polytetrafluoroethylene liner with a capacity of 100ml and seal it in a reactor. Place the reactor sealed with the mixture in an oven, heat it to 200℃ at a heating rate of 10℃ / min, keep it warm for 20h for hydrothermal reaction, and cool it naturally to room temperature after the reaction is completed. Open the reactor, filter the mixed solution after the reaction, wash it with deionized water 3 times, and dry it in an oven at 70℃ to obtain white molybdenum trioxide powder.
[0041] 72 mg of dried molybdenum trioxide powder and 0.88 g of sodium hypophosphite were placed in two arks respectively, the ark containing molybdenum trioxide powder was placed downstream of the tube furnace, and the ark containing sodium hypophosphite was placed upstream of the tube furnace, and H2 / Ar mixed gas with a flow rate of 100 ml / min and a volume fraction of 7% of H2 was introduced, and the temperature was raised to 100°C at a heating rate of 5°C / min, and the air was evacuated after 30 minutes of heat preservation, and then the temperature was raised to 850°C and kept for 2 hours for conversion reaction. After the reaction was completed, the H2 / Ar mixed gas was turned off, and the mixture was cooled to room temperature under the protection of pure Ar atmosphere to obtain molybdenum phosphide / molybdenum (the mass proportion of molybdenum was 18.1%), and the XRD spectrum was as follows: Figure 3 As shown. Molybdenum phosphide / molybdenum and binder polyvinylidene fluoride were added to a grinding mortar at a mass ratio of 8 to 2, and evenly ground for 30 minutes. The mixture was evenly coated with 0.2 mg of molybdenum phosphide on 1 square centimeter of carbon cloth as the positive electrode of the lithium-carbon dioxide battery. The materials were stacked in the order of negative electrode shell, shrapnel, gasket, lithium sheet, diaphragm, positive electrode material, stainless steel mesh and positive electrode shell, and then sealed with a manual hydraulic button battery sealing machine to obtain a lithium-carbon dioxide button battery.
[0042] The button battery was placed in a test bottle filled with carbon dioxide gas, and rate tests were carried out at current densities of 50mA / g, 100mA / g, 200mA / g, 300mA / g, 400mA / g and 500mA / g, and a capacity of 500mAh / g. The charging voltage of the battery was less than 3.7V. A cycle test was carried out under the conditions of a current density of 250mA / g and a capacity of 500mAh / g. The battery stably cycled for 100 times when the charging voltage was less than 4.5V.
[0043] Example 4
[0044] Take 10ml of concentrated sulfuric acid and dissolve it in 50ml of deionized water to obtain a sulfuric acid solution. Weigh 1.4g of sodium molybdate and add it to the sulfuric acid solution. Ultrasonicate it in a 500W ultrasonic instrument for 5min to completely dissolve the sodium molybdate and obtain a mixed solution. After the ultrasonication is completed, transfer the mixed solution into a polytetrafluoroethylene liner with a capacity of 100ml and seal it in a reactor. Place the reactor sealed with the mixture in an oven, heat it to 200℃ at a heating rate of 10℃ / min, keep it warm for 20h for hydrothermal reaction, and cool it naturally to room temperature after the reaction is completed. Open the reactor, filter the mixed solution after the reaction, wash it with deionized water 3 times, and dry it in an oven at 70℃ to obtain white molybdenum trioxide powder.
[0045] 72 mg of dried molybdenum trioxide powder and 1.76 g of sodium hypophosphite were placed in two arks respectively. The ark containing molybdenum trioxide powder was placed downstream of the tube furnace, and the ark containing sodium hypophosphite was placed upstream of the tube furnace. A H2 / Ar mixed gas with a flow rate of 100 ml / min and a H2 volume fraction of 7% was introduced, and the temperature was raised to 100°C at a heating rate of 5°C / min, and the air was evacuated after 30 minutes of heat preservation. The temperature was then raised to 850°C and kept for 2 hours for conversion reaction. After the reaction was completed, the H2 / Ar mixed gas was turned off and cooled to room temperature under the protection of pure Ar atmosphere to obtain molybdenum phosphide. The XRD spectrum is as follows: Figure 4 As shown. Molybdenum phosphide and binder polyvinylidene fluoride were added to a grinding mortar at a mass ratio of 8 to 2, and the mixture was evenly ground for 30 minutes. 0.2 mg of molybdenum phosphide was evenly applied on 1 square centimeter of carbon cloth as the positive electrode of the lithium-carbon dioxide battery. The materials were stacked in the order of negative electrode shell, shrapnel, gasket, lithium sheet, diaphragm, positive electrode material, stainless steel mesh and positive electrode shell, and then sealed with a manual hydraulic button battery sealing machine to obtain a lithium-carbon dioxide button battery.
[0046] The button cell was placed in a test bottle filled with carbon dioxide gas and tested at current densities of 50mA / g, 100mA / g, 200mA / g, 300mA / g, 400mA / g and 500mA / g. The charging voltage of the battery was less than 3.9V ( Figure 6 ); Cycle test was carried out under the conditions of current density of 250mA / g and end capacity of 500mAh / g. The battery cycled stably for 75 cycles when the charging voltage was less than 4.5V ( Figure 7 ).
Claims
1. A method for preparing molybdenum phosphide as a positive electrode for a lithium-carbon dioxide battery, characterized in that It includes the following steps: Step a. Add concentrated acid to deionized water in a certain proportion to prepare an acid solution; Step b. adding the molybdenum source compound to the acid solution, and ultrasonically dissolving the molybdenum source compound in the acid solution to obtain a mixed solution; Step c. Pour the mixed solution in step b into a polytetrafluoroethylene liner, seal the reactor and place it in an oven for heating; Step d. The reaction temperature of the oven in step c is 200°C, the reaction time is 20h, and a white molybdenum source oxide precipitate is obtained, and the molybdenum source oxide is molybdenum trioxide; Step e. placing the molybdenum source oxide obtained in step d downstream of the tubular furnace, and placing the phosphorus source compound upstream of the tubular furnace, wherein the molar ratio of the molybdenum source oxide to the phosphorus source compound is 1:40, heating in an atmosphere of reducing gas and inert gas, the heating temperature is 850 ° C, the reaction time is 1-4h, and trimolybdenum phosphide is obtained; Step f. Take molybdenum phosphide and a binder in a mass ratio of 9:1 and mix them in a grinding mortar, grind them evenly for 30 minutes to fully mix the components, and evenly apply them on a carbon material substrate as a positive electrode for a lithium-carbon dioxide battery.
2. A method for preparing molybdenum phosphide as a positive electrode of a lithium-carbon dioxide battery according to claim 1, characterized in that: In step a, the volume ratio of deionized water to concentrated acid is 5:1, and the concentrated acid is concentrated nitric acid, concentrated sulfuric acid or concentrated nitric acid.
3. A method for preparing molybdenum phosphide as a positive electrode of a lithium-carbon dioxide battery according to claim 1, characterized in that: The molybdenum source compound in step b is ammonium molybdate or sodium molybdate.
4. The method for preparing molybdenum phosphide as a positive electrode of a lithium-carbon dioxide battery according to claim 1, characterized in that: The phosphorus source compound in step e is sodium hypophosphite, the reducing gas is hydrogen, and the inert gas is nitrogen or argon.
5. The method for preparing molybdenum phosphide as a positive electrode of a lithium-carbon dioxide battery according to claim 1, characterized in that: The binder in step f is polyvinylidene fluoride.
Citation Information
Patent Citations
Preparation method of flexible strip-shaped lithium-carbon dioxide battery positive electrode material and battery
CN113659159A
Preparation of carbon-free self-supporting positive electrode membrane material of lithium-carbon dioxide battery and battery
CN114792813A